Giving up the Struggle for Life: J.M. Coetzee’s Life and Times of Michael K and Disgrace - Kucała, Bożena (Department of Dutch and South African Studies, Faculty of English, 2013)
This article discusses two novels by J.M. Coetzee, Life and Times of Michael K and Disgrace, with reference to the Darwinian concept of the struggle for life. The novels depict a world riven by conflict, struggle and competition for resources, which is partly ascribable to the socio-political context of South Africa. In both stories the protagonists are confronted with extreme situations, both facing moments when their survival comes under threat. In the light of Darwinian concepts, Coetzee’s characters fail to adapt to the changing environment and ultimately face extinction. Despite the very significant differences between Michael K and David Lurie – including the degree of their selfunderstanding – they both undergo harrowing experiences, as a result of which they descend to the level of animal existence, retreating to, as Lurie’s daughter puts it, “the only life there is. Which we share with animals.” The implications of the protagonists’ affinity with animals are discussed with regard to Darwin’s claims about the continuities between human and animal life. This article examines the protagonists’ actions and decisions with relation to the biological imperative to struggle for life.
Keywords: J.M. Coetzee; Charles Darwin; struggle for existence; Darwinism in literature